Disaster management in the Philippines experience and viewpoint of school leaders - De Leon, Marietta M. (2008)
This paper presented the results of a study on disaster management conducted at selected schools in the country. It sought to design disaster management strategies and develop models derived from the educational system's experiences. The study employed the sequential transformative strategy as defined by Creswell (2003) and involved qualitative and quantitative paradigms. 34 public and private schools were selected to participate in the study. General findings indicate that most of the schools studied have limited knowledge of hazards and disasters, their knowledge being confined only to those that regularly affect them or those that have affected them. Based on the results, a model, Macro Disaster Management for Educational Institutions in Disaster-Prone Areas, was proposed. Resources constraints limited this study to schools in the Island of Luzon in northern Philippines.
Thesis (Ph.D. Educational Administration)--University of the Philippines, Diliman.
Keywords: Emergency management -- Philippines; Disater relief -- Philippines; Natural disaster -- Philippines